Watermelon Intake on Endurance in Pencak Silat Athletes - Maulana, Ahmad; Jalil, Rasyidah; Saman, Saman (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
This study aims to determine the effect of giving watermelon juice on endurance in pencak silat athletes. The method used is an experiment with 10 samples. The results of the study show that giving watermelon juice have a significant effect on muscle fatigue, anaerobic fatigue, pulse rate, delayed onset muscle soreness, and VO2Max. Physical condition is an important aspect to support the success of an athlete, so proper monitoring of the athlete's physical fitness level is needed. Athletes who play sports to achieve regional, national or international success must have skills specific to the sport they participate in and must be in peak physical condition. This research uses quantitative research methods and experimental research design with pretest and posttest groups. The research population was 20 pencak silat athletes in Luwu and the sample was 10 athletes. This research found that the athlete's physical fitness level was good and could be improved. This study also found that watermelon consumption had a significant effect on endurance. Resources cited in this text cover a wide range of sports-related topics, including the physical and psychological characteristics of athletes, training methods, and the effects of certain foods and training on performance. This study also found that watermelon consumption had a significant effect on endurance. Resources cited in this text cover a wide range of sports-related topics, including the physical and psychological characteristics of athletes, training methods, and the effects of certain foods and training on performance. This study also found that watermelon consumption had a significant effect on endurance. Resources cited in this text cover a wide range of sports-related topics, including the physical and psychological characteristics of athletes, training methods, and the effects of certain foods and training on performance..